Bioactive 3D Scaffolds for the Delivery of NGF and BDNF to Improve Nerve Regeneration - Sandoval-Castellanos, Ana M.; Claeyssens, Frederik; Haycock, John W. (Frontiers in Materials, 2021)
Peripheral nerve injury is an important cause of disability, that can hinder significantly sensory and motor function. The clinical gold standard for peripheral nerve repair is the use of autografts, nevertheless, this method has limitations such as donor site morbidity. An emerging alternative to autografts are nerve guide conduits, which are used to entubulate the severed nerve and provide guidance for the directed regeneration of the nerve tissue. These nerve guide conduits are less effective than autografts, and to enhance their performance the incorporation of neurotrophins can be considered. To enable optimal nerve regeneration, it is important to continuously stimulate neurite outgrowth by designing a delivery system for the sustained delivery of neurotrophins. The aim of this study was to develop a novel bioactive surface on electrospun fibres to supply a sustained release of heparin bound NGF or BDNF electrostatically immobilised onto an amine functionalized surface to encourage neurite outgrowth and Schwann cell migration. The bioactive surface was characterised by XPS analysis and ELISA. To assess the effect of the bioactive surface on electrospun fibres, primary chick embryo dorsal root ganglia were used, and neurite outgrowth and Schwann cell migration were measured. Our results showed a significant improvement regarding nerve regeneration, with the growth of neurites of up to 3 mm in 7 days, accompanied by Schwann cells. We hypothesize that the physical guidance provided by the fibres along the sustained delivery of NGF or BDNF created a stimulatory environment for nerve regeneration. Our results were achieved by immobilising relatively low concentrations of neurotrophins (1 ng/mL), which provides a promising, low-cost, and scalable method to improve current nerve guide conduits.